No sewing until you quilt it - Holmes, Ann R., 1949- (American Quilter's Society, 2012)
"Use the author's 7 patterns or create your own, try out fabrics on a forgiving fusible background, replace patches until you're satisfied, layer, and stitch. Ann's turned-edge technique gives an elegant look to any quilt. No more ripping out stitches because there's no sewing until you quilt"--Provided by publisher.